(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
A 28 year old constable was killed by Motorcycle blast at Alibaug in Raigad District. Initially, it was not confirmed that whether it was bomb blast or blast due to Motor cycle problem. Hence Forensic expert team visited the spot and reconstruct the clue material. It was found presence of detonator cap near to blast site, electrical wire attached to Motor cycle (Honda Unicorn) engine plug and damaged Motor cycle parts. The cotton swab of Motor cycle was taken and analysed which showed presence of Ammonium Nitrate. Hence, it was conclude that the constable was killed by planting a bomb on his Honda Unicorn Motor Cycle.